Association Between NT-proBNP and Prolonged Length of Stay in Hospital Among Preterm Infants Born at 28-31 Weeks' Gestation - Jian Ge; Chenghan Luo; Mengyuan Lei; Zanyang Shi; Zanyang Shi; Zanyang Shi; Xinru Cheng; Xinru Cheng; Xinru Cheng; Min Zhao; Yanting Zhao; Min Song; et al. (Frontiers Media S.A., 2022)
ObjectiveIn the early life of preterm infants, the relationship between heart function and length of hospitalization is unclear. This study aims to examine the association between serum NT-proBNP level on the 7th day (NT-proBNP7) after birth and length of hospitalization among preterm infants.MethodsA retrospective cohort study was conducted. Patients included 709 preterm infants born at 28-31 weeks' gestational age (GA) admitted to the NICU of the First Affiliated Hospital of Zhengzhou University between December 20, 2016, to April 31, 2021. Main outcome: Late discharge (postmenstrual age at discharge was in the fourth quartile (highest) among infants born at the same GA). Exposure factor: NT-proBNP7.ResultsWe observed increased prevalence ratios for late discharge among the tertile of logarithm of NT-proBNP7 level (LnNT-proBNP7) which was positive. Compared with the lowest tertile, infants in the highest tertile of LnNT-proBNP7 had an 8.4-fold increased probability of late discharge, and the results were consistent for the subgroups. Next, a non-linear (S-shaped) relationship between LnNT-proBNP7 and late discharge was observed, whose turning points were 7.5 and 9. The effect sizes and the confidence intervals on the left of the first turning point, between two turning points and on the right of the second turning point, were 0.6 (95% CI, 0.2-1.6), 5.0 (95% CI, 2.4-10.6), and 1.1 (95% CI, 0.2-6.1), respectively. In addition, the prevalence of BPD, NEC, nosocomial infection, or any of them was highest in the group of LnNT-proBNP7 ≥ 9, lowest in the group of LnNT-proBNP7 < 7.5.ConclusionHigher NT-proBNP7 levels were associated with longer hospitalization. The relationship between LnNT-proBNP7 and late discharge was S-shaped. LnNT-proBNP7 was positively related with late discharge when LnNT-proBNP7 was between 7.5 and 9.